Thymoquinone Loaded Solid Lipid Nanoparticles Demonstrated Antidepressant-Like Activity in Rats via Indoleamine 2, 3- Dioxygenase Pathway - Alam, Mahtab; Zameer, Saima; Najmi, Abul Kalam; Ahmad, Farhan Jalees; Imam, Syed Sarim; Akhtar, Mohd (Drug Research, 2020)
The World Health Organization (WHO) has ranked depression the 4th leading cause of disability worldwide. Thymoquinone (TQ), is an active constituent of Nigella sativa having various medicinal properties but has poor solubility and bioavailability. This problem was overcome by developing nanoformulation of TQ. Previously TQ reported good antioxidant and anti-inflammatory effects. Recently TQ’s anti-depressant effect was demonstrated. However, the mechanisms underlying the antidepressant effect of TQ still needs evaluation. Activation of Indoleamine-2,3-dioxygenase (IDO), (an enzyme that participates in the tryptophan metabolism), leads to a decrease of serotonin (5-HT) levels. The expression of this enzyme is associated with immune system activation, which has been proposed as a common mechanism that links depression. The present study was performed in stressed animals where hippocampal levels of pro-inflammatory cytokines (IL-6 and TNF α levels), brain derived neurotropic factor (BDNF) and hippocampal kynurenine (KYN), tryptophan (TRP) and serotonin (5-HT) levels were estimated. Treatment with TQ solid lipid nanoparticles (TQSLN 20 mg/kg p.o) and TQ suspension (20 mg/kg p.o) demonstrated antidepressant-like activity in chronic forced-swim stress model. Further, it reduced the elevated hippocampal IL-6 & TNFα and reversed the increased activity of IDO as measured by ratio of hippocampal KYN/TRP and 5HT/TRP in stressed rats. The results of the present study confirm anti-inflammatory and neuroprotective effects of TQ which may be associated with 5-HT pathway. Thus, the present study offers a newer approach to reduce symptoms of depression using TQSLN. Our results are preliminary, further research is needed for more conclusive view.
Keywords: Depression; Thymoquinone (TQ); Thymoquinone solid lipid nanoparticles (TQSLN); Forced swimming induced stress; Pro-inflammatory cytokines; BDNF